The Influence of Profitability, Solvency, Liquidity Ratios on Company Value: Study on Manufacturing Companies in The Food and Beverage Sub-Sector Listed on The IDX for The 2019-2023 Period - Khumairo Annisa Annisa; Pristin Prima Sari; Johannes Maysan Damanik (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This study aims to determine the effect of profitability, solvency, liquidity on company value in food and beverage sub-sector manufacturing companies listed on the IDX for the 2019-2023 period. This study is a quantitative study using secondary data obtained from the financial statements of food and beverage sub-sector manufacturing companies listed on the IDX for a period of 5 years. The data in this study were processed using IBM SPSS 27.0 Statistics. The results of this study indicate that profitability has a positive effect on company value, solvency does not affect company value, liquidity has a positive effect on company value.